Peculiarities of dynamic processing of high-dispersion and oxidized aluminum wastes - B. M. Nemenenok; V. L. Tribushevsky; S. L. Rimoshevsky; O. N. Kalenik (Литьë и металлургия)
Thе given investigations established positive influence of flux composition, mixing and preparation during processing of dispersion and oxidized wastes of aluminum alloys in short-flame rotary furnace. Substitution of cryolite in chlorine-containing flux with fluorspar is proved advisable.